A Survey to Assess Food Safety Knowledge and Habits Among High School Students, Their Parents and Teachers in Pescara and Chieti Provinces, Abruzzo Region (Italy) - Giulia Colacicco; Gianluca Ciro Telera; Margherita Perilli; Noemi Cortazzi; Luigi Iannetti; Giacomo Migliorati; Fiorenzo Pastoni; Francesco Pomilio; Massimo Sericola; Michela Toro; Ilaria Del Matto; Fabrizio De Massis (Journal of Food Protection, 2023)
Food safety is a topic of increasing relevance in the European Union (EU). Ensuring safe food from farm to fork is one of the main objectives of EU policies. In our study, we conducted an online survey to assess the food safety knowledge and eating habits in various categories. For young people, we chose school students aged 15–19, based on their ability to cook autonomously after school. For adults, we choose a representative sample consisting of students’ parents and teachers in Chieti and Pescara Provinces of Abruzzo Region (Italy). The survey was structured in eight sections with particular attention to questions regarding risks associated with microorganisms (e.g., Salmonella spp.) and bacterial cross-contamination. Students represented 60.7% of all respondents (n = 290). Risk perception associated with microorganisms in food was significantly different among students and teachers (p < 0.05). Students indicated microorganisms as a food risk in 20.2% of cases, while environmental pollutants were considered the greatest problem for 71.7% of participants. Among teachers, results indicated that 55.1% considered microorganisms a food-associated risk. An adequate theoretical knowledge regarding safe cooking practices was demonstrated by the majority of participants. Acceptable knowledge regarding microbiologically safe cooking practices was also demonstrated by participants. Based on these results, we provide suggestions to improve food safety education programs including the use of social media, as well as by adjusting educational strategies according to the background of learners.